PPARα Ameliorates Doxorubicin-Induced Cardiotoxicity by Reducing Mitochondria-Dependent Apoptosis via Regulating MEOX1 - Wang, Wei; Fang, Qin; Zhang, Zhihao; Wang, Daowen; Wu, Lujin; Wang, Yan (Frontiers in Pharmacology, 2020)
Doxorubicin (DOX), which is widely used as chemotherapeutic drug in clinical work, can cause serious cardiotoxicity, and greatly reduce the survival rate, as well as quality of life of chemotherapy patients. Peroxisome proliferation activated receptor α (PPARα) is a kind of ligand activated receptor in the nuclear hormone receptor family that regulates multiple gene expression. Previous studies showed that PPARα possesses anti-apoptotic and cardio-protective effects. However, its role in DOX-induced cardiotoxicity is rarely reported. In this study, we were surprised to find decreased expression of PPARα in the heart of tumor-bearing mice treated by DOX, and there’s no such phenomenon in tumor tissues. Next, we observed that PPARα agonist, fenofibrate (FENO), did not facilitates tumor progression, but enhanced cardiac function in tumor-bearing mice treated by DOX. Subsequently, recombinant adeno-associated virus serotype 9 (rAAV9) was used to manipulate the expression of PPARα in the heart of DOX-induced mice. Our results showed that PPARα gene delivery reduced cardiac dysfunction and mitochondria-dependent apoptosis in DOX-induced mice. Furthermore, we found that PPARα directly regulated the expression of mesenchyme homeobox 1 (MEOX1). Most importantly, cardioprotective effects of PPARα could be neutralized by knocking down MEOX1. In summary, PPARα plays a vital role in DOX-induced cardiotoxicity and is a promising treatment target.